Unveiling the hypotheses of endemic richness: A study case in the Southwestern Alps - Maria Guerrina; Davide Dagnino; Luigi Minuto; Frédéric Médail; Gabriele Casazza (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Will natura 2000 european network of protected areas support conservation of Southwestern Alps endemic flora under future climate? - Gabriele Casazza; Maria Guerrina; Davide Dagnino; Luigi Minuto (Biodiversity and Conservation, 2023)
Networks of protected areas (PAs) are globally recognized as playing a key role for in situ conservation of species. Despite a high potential for biodiversity conservation, PAs may not mitigate the current biodiversity loss because they do not consider climate change impact. In fact, because PAs have static geographical boundaries, they may hardly keep pace with dynamics in species distribution caused by the climate change, which was not considered when they were designed. In this study, we used species distribution modelling of 85 plant taxa endemic or subendemic to Southwestern Alps to evaluate the effectiveness of PAs network in protecting endemics under future climate change scenarios. PAs cover roughly the 30% of the Southwestern Alps. PAs will harbour more expected distribution range of taxa in the future than today, probably because they occur in high altitude areas rich in endemics that have been climatically stable areas in the past and that will likely remain relatively climatically buffered in the future. Moreover, PAs are distributed to poorly cover expected range of endemics at low and middle elevation, which are threatened by urbanization and climate change. We recommend additional protection at low and middle elevation, considering the future climatic suitability of species.

Dealing with disjunct populations of vascular plants: implications for assessing the effect of climate change - Lucia Varaldo; Maria Guerrina; Davide Dagnino; Luigi Minuto; Gabriele Casazza (Oecologia, 2023)
Species distribution models are the most widely used tool to predict species distributions for species conservation and assessment of climate change impact. However, they usually do not consider intraspecific ecological variation exhibited by many species. Overlooking the potential differentiation among groups of populations may lead to misplacing any conservation actions. This issue may be particularly relevant in species in which few populations with potential local adaptation occur, as in species with disjunct populations. Here, we used ecological niche modeling to analyze how the projections of current and future climatically suitable areas of 12 plant species can be affected using the whole taxa occurrences compared to occurrences from geographically disjunct populations. Niche analyses suggest that usually the disjunct group of populations selects the climatic conditions as similar as possible to the other according to climate availability. Integrating intraspecific variability only slightly increases models’ ability to predict species occurrences. However, it results in different predictions of the magnitude of range change. In some species, integrating or not integrating intraspecific variability may lead to opposite trend in projected range change. Our results suggest that integrating intraspecific variability does not strongly improve overall models’ accuracy, but it can result in considerably different conclusions about future range change. Consequently, accounting for intraspecific differentiation may enable the detection of potential local adaptations to new climate and so to design targeted conservation strategies.

Reproductive ecology of Saxifraga florulenta , a monocarpic perennial paleo-endemic of the Alps - Maria Guerrina; Gabriele Casazza; Davide Dagnino; Carmelo Macrì; Enrica Roccotiello; Luigi Minuto (Plant Biosystems, 2022)

First evidence of post‐glacial contraction of Alpine endemics: Insights from Berardia subacaulis in the European Alps - Maria Guerrina; Spyros Theodoridis; Luigi Minuto; Elena Conti; Gabriele Casazza (Journal of Biogeography, 2022)
Aim Late Quaternary glaciations left an enduring imprint on the distribution of species and their genetic structure. The responses of plants endemic to the Alps can be summarized in three major demographic hypotheses: (i) post‐glacial expansion hypothesis; (ii) post‐glacial contraction hypothesis; and (iii) long‐term stability hypothesis. Here we test these hypotheses and reconstruct the time and extent of demographic responses of an endemic plant to the Late Quaternary climate dynamics. Location European Alps. Taxon Berardia subacaulis Vill. (Asteraceae). Methods We used species distribution models to estimate the paleodistribution of B. subacaulis (Asteraceae) throughout the last 28 Ky and generated genome‐wide sequences to estimate current patterns of spatial structure of genetic diversity. We tested five demographic models by integrating the results of the two independent approaches in an Approximate Bayesian Computation framework. Results The species has weak genetic differentiation among populations, with two main genetic groups. Species distribution models showed a reduction in potentially suitable areas for B. subacaulis during the post‐glacial climate warming and demographic models identified a recent split (2.46 Kya) between the two genetic groups and they slightly supported the post glacial contraction hypothesis. Main conclusions Taken together, our results support the post‐glacial contraction of an endemic plant, differing from the main pattern observed for endemics species in the European Alps during the Late Quaternary. The different pattern observed in B. subacaulis might be due to several factors, including the less severe effects of glaciations and the environmental heterogeneity of the South Western Alps, combined with some features of the species (i.e. poor dispersal ability, slow growth and microhabitat preferences). Future research in areas where the ice cover was less extensive will contribute to a more complete understanding of the role of climatic changes in shaping the endemics of the European Alps.

Effects of environmental heterogeneity on phenotypic variation of the endemic plant Lilium pomponium in the Maritime and Ligurian Alps - Carmelo Macrì; Davide Dagnino; Maria Guerrina; Frédéric Médail; Luigi Minuto; John D. Thompson; Gabriele Casazza (Oecologia, 2021)
Geographical limits of species’ distributions are assumed to be coincident with ecological margins, although this assumption might not always be true. Indeed, harsh environments such as Alpine and Mediterranean ecosystems may favour high phenotypic variability among populations, especially those in peripheral sites. Floral traits are often found to be less variable and less affected by environmental heterogeneity than vegetative traits because variation in the former may have negative effects on fitness. For this reason, it is important to quantify variation in floral traits and plant fecundity in study range limits. The objective of the study is to examine phenotypic variation and differences in reproduction in endemic Lilium pomponium in the Maritime and Ligurian Alps in relation to environmental variation across its distribution range. In this species, marginal climatic populations occur both in the peripheral and central geographical locations of the distribution range; hence, geographical and ecological gradients are not concordant. Floral trait variation is related to local environmental conditions with an array of interactions among resource availability, potential pollen limitation and population size that are differentially related to floral traits. Contrary to the general expectation, all central and peripheral populations had similar, moderate seed production with each group limited by different factors acting on different stages of the life-history strategy. Our results are in line with the idea that general expectations are confirmed only when its assumptions are met and that the differences in pollination environment along an environmental gradient may not be the main determinant of the distribution limit.

Climate change and the future of endemic flora in the South Western Alps: relationships between niche properties and extinction risk - Davide Dagnino; Maria Guerrina; Luigi Minuto; Mauro Giorgio Mariotti; Frédéric Médail; Gabriele Casazza (Regional Environmental Change, 2020)
Climate change seriously threatens biodiversity, particularly in mountain ecosystems. However, studies on climate change effects rarely consider endemic species and their niche properties. Using species distribution models, we assessed the impact of climate change on the endemic flora of the richest centre of endemism in the Alps: the South-Western Alps. We projected the potential distributions of 100 taxa under both an optimistic (RCP2.6) and a pessimistic (RCP8.5) climate scenario, analysing the relationships between range dynamics and several predictors (dispersal abilities, vegetation belts, niche marginality, niche breadth, altitudinal range and present range). The negative impact ranged from weak to severe according to the scenario, but the extinction risk was low. The dispersal abilities of species strongly affected these range dynamics. Colline and subalpine species were the most threatened and the relationship between range dynamics and predictors varied among vegetation belts. Our results suggest that the rough topography of the SW Alps will probably buffer the climate change effects on endemics, especially if climate will remain within the limits already experienced by species during the Holocene. The presence of the Mediterranean-mountain flora, less affected by climate change than the alpine one, may explain the lower number of species threatened by extinction in the SW Alps than in other European mountains. These results suggest that the relationship between plants’ sensitivity to climate change, and both niche properties and vegetation belts, depends on the difference between the current climate in which species grow and the future climate, and not just on their niche breadth.

Reproductive biology of the threatened Lilium pomponium (Liliaceae), a species endemic to Maritime and Ligurian Alps - Gabriele Casazza; Angelino Carta; Paolo Giordani; Maria Guerrina; Lorenzo Peruzzi; Luigi Minuto (Journal of Plant Research, 2018)

Reproductive biology of an Alpic paleo-endemic in a changing climate - Maria Guerrina; Gabriele Casazza; Elena Conti; Carmelo Macrì; Luigi Minuto (Journal of Plant Research, 2016)

Knowing the past to forecast the future: a case study on a relictual, endemic species of the SW Alps, Berardia subacaulis - Maria Guerrina; Elena Conti; Luigi Minuto; Gabriele Casazza (Regional Environmental Change, 2016)

Pollination ecology in the narrow endemic winter-flowering Primula allionii (Primulaceae) - Luigi Minuto; Maria Guerrina; Enrica Roccotiello; Nicolò Roccatagliata; Mauro Giorgio Mariotti; Gabriele Casazza (Journal of Plant Research, 2014)